MEK inhibitors for the treatment of NRAS mutant melanoma - Sarkisian S; Davar D (Dove Medical Press, 2018)
Saro Sarkisian,1 Diwakar Davar2 1Division of General Internal Medicine, University of Pittsburgh, Pittsburgh, PA, USA; 2Division of Hematology-Oncology, Hillman Cancer Center and University of Pittsburgh, Pittsburgh, PA, USA Abstract: Melanoma is increasing rapidly in incidence and prevalence, especially in younger females and older males. Treatment options have expanded beyond high-dose interleukin 2 and adoptive T-cell therapy to include inhibitors of immune checkpoints programmed death 1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and small molecular inhibitors of pathways activated in melanoma, in particular the mitogen-activated protein kinase (MAPK) pathway. PD-1/CTLA-4 inhibitors and inhibitors of MAPK such as BRAF/MEK inhibitors have significantly improved survival in both the metastatic and, more recently, adjuvant settings. In this review, we discuss the preclinical data, clinical development, and potential use of novel MEK inhibitor binemetinib, particularly in the setting of NRAS mutant melanoma. Keywords: advanced, metastatic, melanoma, BRAF, MEK, NRAS, binimetinib, MAPK, ERK